Looking emotionally: photography, racism and intimacy in research. - Figueroa, Mónica G. Moreno (History of the Human Sciences, 2008)
In this article I argue the need for a reflexive use of photographic images in research, mainly in the publication and dissemination phase and specifically when the topic investigated relates to issues of visibility, in this case racism and understandings of beauty. This analysis draws on my work on contemporary practices of racism in Mexico, where personal photographs were used as research tools in life-story interviews, creating a sense of shared intimacy. Inspired by Barthes' refusal in Camera Lucida (2000) to reproduce a photograph of his mother, in this article I focus on the dynamics between seeing and looking and suggest that 'looking emotionally' at both participants' accounts and their photographic images, is a way to address the complexities of the gaze and discuss the specificity of different 'ways of looking'. The notion of 'looking emotionally' refers to an engagement, of researchers and audiences of research, with participants' lived emotional experiences that explicitly confronts the historical and social legacies of the visible. Here, photographs are understood not only as illustrative platforms from where experiences are organized, but also as 'traps' that both inform and ensnare (Gell, 1999). As such, the argument aims to problematize the intimate relationship between gaze and photographic image in a context where racism is constrained to the visible, both in its reproduction and also in its pressing ongoing critique.